Effect of cooperative learning and peer tutoring on performance in biology among students with hearing impairment in Ibadan, Oyo State, Nigeria (2020)
Specialized instructional techniques are believed to have the required potency to enhance the academic performance of learners with hearing challenges in the school system. However, reports have shown that some of the techniques were not effective in enhancing the academic performance of students with disabilities offering science subjects. Thus, this study was therefore designed to investigate the impact of co-operative learning and peer tutoring on Biology performance among students with hearing impairment in Ibadan, Oyo State, Nigeria. The study adopted a pretest-posttest, control group, quasi-experimental research design with a 3x2x2 factorial matrix. Three special secondary schools were randomly selected and purposive sampling was used in selecting fifty (50) Senior Secondary School Two students with hearing impairment, comprising thirty (30) males and twenty (20) females. These students were randomly assigned into Experimental Group I (17), Experimental Group II (16) and Control (17). Biology Achievement Test Questionnaire (BATQ; r=0.87) and General Self-efficacy Scale (GSS; r=0.60) were the major instruments used for the study. Participants in the experimental groups were taught Biology with the instructional strategies while those in control group were instructed using the conventional method. Seven hypotheses were raised and tested at 0.05 level of significance, while data were analyzed, using Analysis of Covariance (ANCOVA) and mean scores. There was a significant main effect of treatment on the participant’s performance in Biology (F(2.42)) = 21.32; Partial η2= 0.50). Co-operative learning and peer tutoring were effective in enhancing the participant’s performance in Biology. The participants exposed to peer tutoring had the highest mean score (23.60), followed by those in co-operative learning (17.76), while those in the control group, had the lowest mean score (13.20). The two-way interaction effects of treatment and self-efficacy was significant (F(1.42)= 13.80, P<.05, η2=.43) in favour of participants exposed to peer tutoring, although the interaction effects of treatment and gender were not significant (F(1.42) = .420, P>.05, η2 = 0.16). The three-way interaction effect of treatments, gender and self-efficacy on performance in Biology was significant (F(1.42) = 17.480, P<.05, η2=.30). Based on these findings, peer tutoring and cooperative learning should be incorporated into the teaching of students with hearing impairment, especially in teaching Biology in secondary schools. Attention should also be paid to academic self-efficacy of female students by the teachers and the guidance counsellors so that their learning can be positively impacted upon.